MIR-338-3P DOWN-REGULATION IN SMALL ARTERIES OF HYPERTENSIVE PATIENTS WITH CHRONIC KIDNEY DISEASE MAY ACT VIA UP-REGULATION OF ALKALINE CERAMIDASE 2 AND GLUTATHIONE PEROXIDASE 3. (April 2021) - Paradis, Pierre; Mahjoub, Nada; Huo, Ku-Geng; Berillo, Olga; Richer, Chantal; Fraulob-Aquino, Julio C.; Briet, Marie; Boutouyrie, Pierre; Lipman, Mark L.; Sinnett, Daniel; Schiffrin, Ernesto L
Abstract : Objective: Hypertension (HTN) is associated with vascular damage characterized by vascular remodeling and stiffening and endothelial dysfunction, which is a cause of end-organ damage such as chronic kidney disease (CKD). microRNAs are small non-coding RNA that regulate gene expression by binding to their target messenger RNAs (mRNAs), leading to mRNA degradation or translational repression. Their participation in mechanisms leading to vascular injury remains unclear. We aimed to identify differentially expressed (DE) microRNAs in small arteries of human subjects with HTN associated or not with CKD to gain insight into pathophysiological molecular mechanisms in these conditions. Design and method: Normotensive subjects and patients with HTN associated or not with CKD grades 3-4 were studied (n = 15-16). Blood pressure was determined by automated office measurement (AOBP). Small arteries were isolated from subcutaneous gluteal biopsies and RNA extracted for small and total RNA sequencing using Illumina HiSeq-2500. Differentially expressed (DE) genes were identified with a P < 0.05. The selected DE miRNAs were confirmed by reverse transcription-quantitative PCR (RT-qPCR). Putative microRNA targets were validated using gain- and loss-of-function in human aortic vascular cells by RT-qPCR and luciferase reporter assay. Results: Small RNA sequencing identified DE microRNAs uniquely associated with HTN (3 up and 6 down), CKD (42 up and 39 down) or both groups (2 up). One of 14 tested DE microRNAs was validated. RT-qPCR showed that miR-338-3p was decreased by 59% in CKD (P < 0.05). miR-338-3p and three of its predicted targets were highly expressed in human aortic endothelial cells (HAECs). Two of them, alkaline ceramidase 2 (ACER2) and glutathione peroxidase 3 (GPX3), were up-regulated by 48% and 90% in human aortic endothelial cells (HAECs) transfected with anti-miR-338-3p, respectively (P < 0.05). miR-338-3p mimic co-transfection in HAECs decreased respectively by 13% and 24% luciferase activity of reporter vectors containing the conserved wild-type but not mutated ACER2 or GPX3 3' untranslated transcribed region miR-338-3p-5p binding sites (P < 0.05). Conclusions: miR-338-3p down-regulation in small arteries may act via mRNA up-regulation of alkaline ceramidase 2 and glutathione peroxidase 3 to play a role in vascular injury in hypertensive patients with chronic kidney disease.